3(2x+1)+13x-12=18x-3

Simple and best practice solution for 3(2x+1)+13x-12=18x-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2x+1)+13x-12=18x-3 equation:


Simplifying
3(2x + 1) + 13x + -12 = 18x + -3

Reorder the terms:
3(1 + 2x) + 13x + -12 = 18x + -3
(1 * 3 + 2x * 3) + 13x + -12 = 18x + -3
(3 + 6x) + 13x + -12 = 18x + -3

Reorder the terms:
3 + -12 + 6x + 13x = 18x + -3

Combine like terms: 3 + -12 = -9
-9 + 6x + 13x = 18x + -3

Combine like terms: 6x + 13x = 19x
-9 + 19x = 18x + -3

Reorder the terms:
-9 + 19x = -3 + 18x

Solving
-9 + 19x = -3 + 18x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-18x' to each side of the equation.
-9 + 19x + -18x = -3 + 18x + -18x

Combine like terms: 19x + -18x = 1x
-9 + 1x = -3 + 18x + -18x

Combine like terms: 18x + -18x = 0
-9 + 1x = -3 + 0
-9 + 1x = -3

Add '9' to each side of the equation.
-9 + 9 + 1x = -3 + 9

Combine like terms: -9 + 9 = 0
0 + 1x = -3 + 9
1x = -3 + 9

Combine like terms: -3 + 9 = 6
1x = 6

Divide each side by '1'.
x = 6

Simplifying
x = 6

See similar equations:

| -1=x/3-7 | | 2-6x=-88 | | 16=6x+40 | | -(4y+2)-(-3y-8)=2 | | 4x+20=(x+3) | | 15d+2=9d+26 | | -7x^2-57x-8=0 | | 5z+(6+2z)=-43 | | 9/7t=-7/2 | | 3(a+8)=33.6 | | 1.5x+1=5-2x | | 49/7x60/2x5 | | 15x+(x+2)=10+6x+(-x+3) | | X/p+x/q=a | | 1/2(2t+3)=2/3(6t-1) | | 16=7x | | 3/2x+1=5-2x | | 3=2c-4 | | -16=-4/3X | | 3e-1=15.8 | | 3p=25.8 | | 2x+8=3x+14 | | 2*1/5/4/5 | | 0/47x10x3 | | 3w^2-13w=10 | | 21/5/4/5 | | 6(a+1)=36 | | f/5+5=-7 | | 2x-5+7x=-32 | | m/6-5/8=7/8 | | 4e-8=16 | | -(5y+1)-(4y-6)=3 |

Equations solver categories